Qualitative Interviewing of Respondents in Large Representative Surveys - Olaf Groh-Samberg; Ingrid Tucci (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2010)
Large representative surveys are using mixed methods to an ever-increasing degree. Biomarkers, register data, and experiments, for example, provide different types of data that can be linked with survey data. The use of qualitative interviewing of participants in longitudinal surveys is still rare, however, in the social sciences. Yet qualitative methods have proven just as valuable as quantitative methods in providing insights into social reality by reflecting the multidimensionality of individual life courses and lived realities. Furthermore, indepth interviews can provide a better understanding of individual decision-making processes and behavior resulting from more or less unconscious strategies. They also provide insights into decisive turning points in people's lives. Finally, by linking quantitative and qualitative data, the reliability of longitudinal information can be analyzed thoroughly in terms of accuracy as well as meaningfulness.
Keywords: C81; C83; Z13; 330; mixed methods; qualitative data; longitudinal data; life course